Development and validation of RP-HPLC method for analysis of multicomponent cough-cold syrup formulation - Ivković Branka; Marković Bojan; Vladimirov Sote (Pharmaceutical Association of Serbia, Belgrade, Serbia, 2014)
In this study a reversed phase HPLC method for rapid and simultaneous identification and quantification of doxylamine succinate, ephedrine sulfate, dextrometorphane hydrobromide, paracetamole and sodium benzoate in cough-cold syrup formulation was described. Separation was carried out on XTerraTM RP 18, Waters (150 mm x 4.6 mm column, 5 μm particle size). For the analysis of investigated substances gradient elution was used employing water, pH adjusted at 2.5 with 85 % ortophosphoric acid as the mobile phase A and acetonitrile as the mobile phase B. Detection was carried out by UV absorbance at 210 nm for doxylamine succinate, ephedrine sulfate, dextromethorphane hydrobromide and sodium benzoate and at 270 nm for paracetamole. The method was validated statistically for selectivity, linearity, precision, accuracy.